"Dirty Love": Frank Zappa and the Antithetical Love Song. Issue 1 (2nd January 2018) - Schmalenberger, Sarah
Abstract: American composer and guitarist Frank Zappa hated love songs. Relegating them to "everybody else's department, " Zappa parodied them instead. His method of musical pastiche aptly caricatured cliché sentiments as a form of genre critique. His exposure of the banalities of love songs launched an internal revolt within rock-and-roll practice while still preserving the subversive archetypes of the genre. Zappa's cynicism about love songs pilloried a music industry that acquiesced to the mind-set of mass-culture tastes. While other artists flooded the airwaves with vacuous sentimentality, Frank Zappa responded in especially rich oppositional tones by saying, as he sang in 1966, "Go Cry on Somebody Else's Shoulder."  American composer and guitarist Frank Zappa hated love songs. Relegating them to "everybody else's department, " Zappa parodied them instead. His musical pastiches aptly caricatured cliché sentiments as a form of genre critique. This launched an internal revolt within rock-and-roll practice for preserving the subversive archetypes of the genre to criticize content. Zappa's cynicism about love songs pilloried a music industry that acquiesced to the mind-set of mass-culture tastes. While other artists flooded the airwaves with vacuous sentimentality, Frank Zappa responded in especially rich oppositional tones by saying, as he sang in 1966, "Go Cry on Somebody Else's Shoulder.